Views of young, rural African Americans of the role of community social institutions in HIV prevention. - Akers, Aletha Y; Youmans, Selena; Lloyd, Stacy W; Smith, Dionne M; Banks, Bahby; Blumenthal, Connie; Albritton, Tashuna; Ellison, Arlinda; Smith, Giselle Corbie; Adimora, Adaora A (Journal of health care for the poor and underserved, 2010)
We explored rural African American youths' perceptions about the role of community social institutions in addressing HIV.
Keywords: Adolescent; African Americans; Attitude to Health; Community Health Centers; Community Health Services; Community-Institutional Relations; Female; Focus Groups; Health Services Accessibility; HIV Infections; Humans; Male; North Carolina; Politics; Religion; Rural Population; Schools; Young Adult